2017
DOI: 10.1016/j.jad.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Generating an efficient version of the Edinburgh Postnatal Depression Scale in an urban obstetrical population

Abstract: Background Postpartum depression incurs significant burden and suffering. Methods We investigated the latent structure of the most commonly used screening measure, the Edinburgh Postnatal Depression Scale (EPDS) in women (N = 15,172) and tested its predictive validity for the diagnosis of depression as determined with a structured clinical interview. Exploratory and confirmatory factor analyses, Receiver Operating Characteristic curves, and logistic regression analyses were conducted. Results A seven-item … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…The EPDS (J. L. Cox et al., 1987 ) is a 10-item self-report screening tool measure of PND. The cut-off criteria for screening has been noted to vary between studies and clinical populations ( Gollan et al., 2017 , Matthey and Agostini, 2017 ), however, the ‘classic’ cut-point threshold is 12/13for probable PND (J. L. Cox et al., 1987 ). A 9/10 cut-point for screening has been suggested (J.L.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The EPDS (J. L. Cox et al., 1987 ) is a 10-item self-report screening tool measure of PND. The cut-off criteria for screening has been noted to vary between studies and clinical populations ( Gollan et al., 2017 , Matthey and Agostini, 2017 ), however, the ‘classic’ cut-point threshold is 12/13for probable PND (J. L. Cox et al., 1987 ). A 9/10 cut-point for screening has been suggested (J.L.…”
Section: Methodsmentioning
confidence: 99%
“…Despite, the extensive use of the EPDS as a screening instrument, the measure has also been noted for some contradictory observations in terms of its measurement structure. The measure itself was originally developed to be a unitary measure of (postnatal) depression, however, a multitude of studies have demonstrated the EPDS to have an underlying multi-dimensional factor structure ( Brouwers et al., 2001 , Gollan et al., 2017 , Jomeen and Martin, 2007 , Matthey, 2008 , Phillips et al., 2009 , Reichenheim et al., 2011 , Ross et al., 2003 , Tuohy and McVey, 2008 ). The findings of such studies constructively suggest that the EPDS may comprise sub-scale domains of potential and added clinical value ( Matthey, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations